ANALISIS KEPATUHAN DAN AKUNTABILITAS ATAS LAPORAN PEMBERI SUMBANGAN DANA KAMPANYE (LPSDK) PADA PARTAI POLITIK KPU PROVINSI SULAWESI - Meivia Permata, Yastika Maulidiya; Wilasittha, Acynthia Ayu (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Campaign activities have funds that are used to fulfill whatever is needed at the time the activity takes place. The funds obtained come from political parties, legislative candidates, as well as donations from other parties that are legal in accordance with established laws. The aim of this research is to determine the level of compliance and accountability for donations obtained by political party election participants by ensuring donation regulations, reporting donations, and monitoring and auditing campaign fund donations. The research was conducted at the Public Accounting Firm (KAP) which focused on one of the political parties in the North Sulawesi KPU. Thus, the research method used is qualitative descriptive research which will explain the compliance of political party election participants in reporting donations received and disbursed, by examining supporting documents for reporting campaign fund donations and recalculating campaign fund donations. Compliance and accountability for campaign fund donations from the three districts in the North Sulawesi KPU are still considered lacking. This is due to compliance indicators that have not been met by one of the districts, related to the date and time of the Campaign Fund Contribution Report (LPSDK) submitted to the KPU. As a result of this delay, the KPU did not provide a receipt as proof that the district had submitted campaign fund donations in accordance with applicable regulations. So, there needs to be improvements for political parties to set stricter internal schedules for collecting and reporting campaign funds.